Description Of Hospitalization Stress Of Children's Age Pre-School - Asnidar; Haerati; Hilmi Nurfadillah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Preschool children are children who are vulnerable to stress because the child's ability to treat stress is still limited where hospitals can be stressful for children, so children will increase the stress of hospitalization. Hospitals can be adjusted by several factors, one of which is caring for nurses. The purpose of this study was to study the stress level of pre-school age children's hospitals in the Mawar Room and Pavilion of H.Andi Sulthan Daeng Radja Hospital in Bulukumba Regency. The research design used was a descriptive survey with a total sample of 30 respondents. The results showed that changing the stress of hospitalization was predominantly male by 20 respondents (66.7%), children who had never been hospitalized as many as 25 respondents (83.3%) and the majority of children who experienced stress hospitalization were 18 respondents ( 60%). From the research it can be concluded that hospital stress can be carried out on all boys and girls, both children who are hospitalized for the first time or who have been repeatedly hospitalized, so that it is recommended to the organizations concerned to improve service especially in discussions at the pavilion's nursing home. and roses by creating a pleasant atmosphere, making room arrangements that can reduce stress in children who are cared for care.